EFEKTIFITAS PEMANFAATAN USG TERHADAP PEMERIKSAAN IBU HAMIL DI PUSKESMAS PAMANDEGAN TAHUN 2023 - Ekayanti, Ekayanti; Rohmawati, Mega (LPPM STIKES BINA GENERASI POLEWALI MANDAR, 2024)
Ultrasound, also known as ultrasound, is an examination in the field of diagnostic support. The usefulness of ultrasound can be obtained by utilizing high-frequency ultrasonic waves to produce images from inside the body. This study aims to determine the effectiveness of the use of ultrasound for the examination of pregnant women in nursing centers in 2023. The design of this study is Cross sectional Primary data was taken by performing questionnaire filling. The study will be conducted in December 2023. The sample in this study was a pregnant woman who checked her pregnancy and came to visit Pamandegan Health Center during the study period. Researchers will take samples with a purposive sampling technique and a minimum target sample of 30 people. The results of chi square analysis showed a p value of 0.049 because the p value < 0.05, it can be concluded that there is a significant influence between routine pregnancy examination and the use of ultrasound by pregnant women in Pemandegan Health Center. The OR value is 4.67, which means that pregnant women who regularly perform ANC are more likely to have an ultrasound examination 4.6 times than those who do not regularly perform ANC.